Inflation dynamics: Profits, wages and import prices - Yilmaz, Ensar; Bulut, Necip (ELSEVIER, 2025)
This study adds to the ongoing debate over the rise in inflation in Turkiye during the 2021-2023 period, by identifying its root causes, distributive consequences, and the mechanisms through which inflation spreads. By adopting a framework that emphasizes the foreign exchange rate pass-through effect (cost-push) and distributive conflict, we investigate the role of profit-driven inflation, increasing profit shares, markups, and rising import costs. Specifically, we examine how escalating import costs can affect profit shares and spread inflation, even without a wage-price spiral. To explore these dynamics, the study uses descriptive statistics, sectoral data, and decomposition techniques to shed light on the drivers of inflation and its distributive effects. Additionally, the structural vector autoregression (SVAR) methodology is applied, leveraging quarterly data from 2013 Q1 to 2023 Q4. The results highlight that shocks to import prices have a substantial and persistent impact on inflation and profit shares, particularly between 2018 and 2023. In contrast, the effect of wages on inflation is found to be negligible throughout this period.
Keywords: Conflict theory; cost-push; income distribution; markup; profit inflation; Turkiye; LABOR SHARE; OUTPUT GAP; CONFLICT; RISE; Business & Economics